2021
DOI: 10.1016/j.mcpro.2021.100088
|View full text |Cite
|
Sign up to set email alerts
|

TMEM67, TMEM237, and Embigin in Complex With Monocarboxylate Transporter MCT1 Are Unique Components of the Photoreceptor Outer Segment Plasma Membrane

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
1
19
2
Order By: Relevance
“…ABCA4 protein was clearly expressed in wild-type ROs and its localization was confined to the outer segments of retinal photoreceptors, as observed in the human retina. ABCA4 was much less present in the outer segment when compared to rhodopsin, which is in line with earlier observations conducted in mouse rod cells where the molar ratio of ABCA4 to rhodopsin was 1:300 (Skiba et al 2021). The protein assays in STGD1 ROs that underwent the AON treatment confirmed the utility of ROs as in vitro model for STGD1; we confirmed that the rescued protein is trafficked and co-localizes in outer segments of photoreceptor cells.…”
Section: Discussionsupporting
confidence: 92%
“…ABCA4 protein was clearly expressed in wild-type ROs and its localization was confined to the outer segments of retinal photoreceptors, as observed in the human retina. ABCA4 was much less present in the outer segment when compared to rhodopsin, which is in line with earlier observations conducted in mouse rod cells where the molar ratio of ABCA4 to rhodopsin was 1:300 (Skiba et al 2021). The protein assays in STGD1 ROs that underwent the AON treatment confirmed the utility of ROs as in vitro model for STGD1; we confirmed that the rescued protein is trafficked and co-localizes in outer segments of photoreceptor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Some essential CC-resident proteins, such as RPGR orf15 ( 73 ) and RPGRIP1 ( 74 ), localize to centrioles in other cell types ( 75 ), and others, such as SPATA7 ( 36 ), are missing or nonessential in TZ of other cilia. It was recently reported ( 76 ) that MKS3/TMEM67, which is considered a marker of the TZ in primary cilia ( 18 , 49 , 50 ), is found at the base of and throughout the plasma membrane of rod outer segments, suggesting photoreceptor-specific location and function, which bears further investigation. We show here that the well-characterized TZ marker, NPHP8, locates to a narrow region at the base of the CC, as in other cilia, and not throughout the entire CC length ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 91%
“…The goal of this study was to determine the absolute amounts of proteins that perform phototransduction or otherwise uniquely reside in the photoreceptor disc membranes where phototransduction takes place. We only included proteins that were documented to produce at least two unique tryptic peptides confidently identified by mass spectrometry in our previous studies (10,22,25,26). This allowed us to analyze 16 proteins directly engaged in phototransduction (entries 1-16 in Supplementary Table 1) and four additional disc-specific proteins (entries [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…A more accurate mass spectrometry-based approach for absolute protein quantification involves the use of commercially synthesized isotope labeled peptide standards corresponding to tryptic fragments of a protein of interest. To our knowledge, this technique has only been applied to quantifying a handful of outer segment proteins in a single study (10). The limited use of this approach is due, at least in part, to the high costs of labeled peptide standards, potential issues with the stability and solubility of these peptides and the fact that concentrations of many commercial peptide standards are not easy to independently verify in a quantitatively consistent manner (11).…”
Section: Introductionmentioning
confidence: 99%